Caloric Restriction and Ketogenic Diet Therapy for Epilepsy: A Molecular Approach Involving Wnt Pathway and KATP Channels - Rubio, Carmen; Luna, Rudy; Rosiles, Artemio; Rubio-Osornio, Moisés (Frontiers in Neurology, 2020)
Abstract Epilepsy is a neurological disorder which in many cases there is poor pharmacological control of seizures. Nevertheless, it may respond beneficially to alternative treatments such as dietary therapy, like the ketogenic diet or caloric restriction. One of the mechanisms of these diets is to produce a hyperpolarization mediated by the adenosine triphosphate (ATP)-sensitive potassium (KATP) channels (KATP channels). Extracellular increase of K+ prevents the release of Ca2+ by inhibiting the signaling of the Wnt pathway and the translocation of β-catenin to the cell nucleus. Wnt ligands hyperpolarize the cells by activating K+ current by Ca2+. Each of the diets described in this paper has in common lower use of carbohydrates, which leads to biochemical, genetic processes presumed to be involved in the reduction of epileptic seizures. Currently, there is not much information about the genetic processes implicated, as well as possible beneficial effects of diet therapy on epilepsy. In this review, we aim to describe some of the possible genes involved in Wnt pathways, their regulation through the KATP channels which are implicated in each one of the diets, and how they can reduce epileptic seizures at the molecular level.